Core-shell spheroidal microparticles with polystyrene cores and rich in polyglycidol shells. (20th June 2018) - Komar, Patrycja; Gosecka, Monika; Gadzinowski, Mariusz; Gosecki, Mateusz; Makowski, Tomasz; Slomkowski, Stanislaw; Basinska, Teresa
Abstract: This paper describes the preparation of spheroidal polystyrene core and polyglycidol-rich microparticles by stretching the relevant core-shell microspheres embedded into the poly(vinyl alcohol) film. The requirements for the preparation of the defect-free core-shell spheroids were determined. The rearrangement of the microparticle interfacial layer accompanying the conversion of the microspheres into microspheroids is described. Graphical abstract: Image 1 Highlights: The aspect ratio of spheroids is equal to the relative film elongation. The uniaxial thermostretching of particles affected particles surface morphology. The spherical domains on the particles surface underwent reorientation. The elongated particles' aspect ratio conforms well to equation derived for spheroids.